Microenvironmental Th9 and Th17 lymphocytes induce metastatic spreading in lung cancer - Salazar Montano, Ylia; Zheng, Xiang; Brunn, David; Raifer, Hartmann; Picard, Felix; Zhang, Yajuan; Winter, Hauke; Guenther, Stefan; Weigert, Andreas; Weigmann, Benno; Dumoutier, Laure; Renauld, Jean-Christophe; et al. (The journal of clinical investigation, 2020)
Immune microenvironment plays a critical role in lung cancer control versus progression and metastasis. In this investigation, we explored the effect of tumor-infiltrating lymphocyte subpopulations on lung cancer biology by studying in vitro cocultures, in vivo mouse models, and human lung cancer tissue. Lymphocyte conditioned media (CM) induced epithelial-mesenchymal transition (EMT) and migration in both primary human lung cancer cells and cell lines. Correspondingly, major accumulation of Th9 and Th17 cells was detected in human lung cancer tissue and correlated with poor survival. Coculturing lung cancer cells with Th9/Th17 cells or exposing them to the respective CM induced EMT in cancer cells and modulated the expression profile of genes implicated in EMT and metastasis. These features were reproduced by the signatory cytokines IL-9 and IL-17, with gene regulatory profiles evoked by these cytokines partly overlapping and partly complementary. Coinjection of Th9/Th17 cells with tumor cells in WT, Rag1-/-, Il9r-/-, and Il17ra-/- mice altered tumor growth and metastasis. Accordingly, inhibition of IL-9 or IL-17 cytokines by neutralizing antibodies decreased EMT and slowed lung cancer progression and metastasis. In conclusion, Th9 and Th17 lymphocytes induce lung cancer cell EMT, thereby promoting migration and metastatic spreading and offering potentially novel therapeutic strategies.
Gesehen am 11.01.2021